Some Patterns of Haemostatic Parameters Among Pregnant Women with Hypertensive Disorders in Owerri, Imo State, Nigeria - Johnkennedy Nnodim; Okoroiwu Leticia Ijeoma; Nwosu Dennis; Nnodim Johnkennedy; Ilona Emeka; Nkemka Orajiaka-Uchegbu Chizoba; Ezechi Ruphina Ukamaka; Uhiara Raphael Osinachi (Journal La Medihealtico, 2022)
Hemostatic parameters of pregnant women with hypertensive disorders in owerri were studied using standard methods. The parameters include PT, APTT, Fibrinogen, t-PA, D-dimer. A total of 200 pregnant women between ages of 18 and 45 years of age were recruited for the study. They consisted of 50 normotensive pregnant women as the control group and 150 hypertensive as the test subjects. The test group was further divided into 3 viz; 50 chronic hypertensive, 50 gestational and 50 preeclamptic pregnant women as group as groups 1, 2 and 3 respectively. The mean PT(secs.) values were 11.69±1.02, 11.98±0.94, 12.79±0.78 and 13.86±1.4 respectively, in control, groups 1, 2 and 3. The APTT(secs) mean values in control, groups 1, 2 and 3 were 28.59±2.33, 29.43±2.67, 30.20±2.73 and 31.52 respectively. The mean values obtained for D-dimer (ng/ml) were 191.72±41.92, 207.30±60.71, 249.52±62.08 and 268±59.51 in control, groups 1, 2 and 3 respectively. In control, fibrinogen (mg/ml) mean value obtained was 521.74±118.02, where as in the test groups, 532.97±111.40, 602.52±103.80 and 671.98±97.37 were respectively obtained in groups1, 2 and 3. The mean respective values of t-PA (ng/ml) in control, group 1, 2 and 3 were 2.43±0.55, 2.49±0.49, 2.84±0.54 and 2.90±0.57. All the haemostatic parameters: PT, APTT, Fibrinogen, D- dimer and t-PA values increased across the test groups when compared with the control groups and they were found to be statistically significant (P=0.0001). From this study, haemostatic parameters increased in the test subjects indicating inflammatory activities in hypertensive disorders of pregnancy.